Literature Mapping and Research Trends on Smallholder Oil Palm Replanting - Rizqi Sari Anggraini; Harianto Harianto; Arif Imam Suroso; Tanti Novianti (Jurnal AGRISEP, 2026)
Oil palm replanting is critical for maintaining yields, improving farmer livelihoods, and reducing expansion to forested areas. Indonesia’s smallholder farmers manage a large proportion of the national plantations but face declining productivity due to aging trees and substantial constraints in replanting programs. This study presents a systematic literature review of research published between 2015 and 2024 on smallholder oil palm replanting in Indonesia. Using PRISMA-based screening, this study applied Open Knowledge Maps and VOSviewer to examine research trends, thematic clusters, and knowledge gaps. The analysis identified five dominant themes: environmental impacts, biomass economic valuation, corporate farming schemes, institutional arrangements, and community-driven initiatives. Environmental studies focus on biodiversity and greenhouse gas emissions, whereas economic research examines subsidy effectiveness and productivity. Institutional analyses highlight policy frameworks and extension services, while community-oriented research explores farmer participation, collective action, and risk preferences. Despite increasing scholarly attention, major gaps remain in understanding replanting profitability, behavioral decision-making under risk, effective support mechanisms, and integrated sustainability dimensions. This study provides a comprehensive research map and outlines priorities for strengthening sustainable replanting strategies for Indonesian smallholders.